2018
DOI: 10.1002/slct.201702534
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl‐Terminated Dendrimer Acting as a High Exhaustion Agent for Chrome Tanning

Abstract: Severe restrictions for chromium discharge and scarcity of chromium resources have forced the tanners to seek for lowwaste and high exhaust chrome tanning technology. Based on the structural traits of dendrimers, in this paper, a series of hydroxyl terminated dendrimers (HTD) with different molecules weight (Mw) was synthesized and applied in the chrome tanning of pigskin. The effect of HTD was investigated on chromium discharge in effluent, and on the shrinkage temperature (Ts), denaturation temperature (Td),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…It has been reported to be an excellent chromium exhausting agent. 23,24 Previous studies have confirmed the tanning properties and biodegradability of epoxy-terminated branched macromolecules used as a main tanning agent. 25 In this paper, EHBP has been used as a pre-tanning agent (or a pickling auxiliary) to develop a new technology of salt-free pickling and combination tanning (Fig.…”
Section: Introductionmentioning
confidence: 90%
“…It has been reported to be an excellent chromium exhausting agent. 23,24 Previous studies have confirmed the tanning properties and biodegradability of epoxy-terminated branched macromolecules used as a main tanning agent. 25 In this paper, EHBP has been used as a pre-tanning agent (or a pickling auxiliary) to develop a new technology of salt-free pickling and combination tanning (Fig.…”
Section: Introductionmentioning
confidence: 90%